2007
DOI: 10.1002/ccd.20916
|View full text |Cite
|
Sign up to set email alerts
|

Impact of three‐dimensional characteristics of the left main coronary artery bifurcation on outcome of crush stenting

Abstract: Overlap of the LAD stent over, as opposed to under, the LCX stent was associated with close apposition of the stent to the vessel on the myocardial side, at the ostium of the LCX artery, where atherosclerotic plaques are likely to be present. The spatial plaque burden and bifurcation angle should be closely examined before crush stenting, and segments should not be left unstented over large plaques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…The model used in these studies has been previously described [13]. Briefly, it consists of a 4-mm diameter silicon tube, corresponding to the left anterior descending (LAD) artery, glued along the long axis of a 7.5-cm diameter column, and a second, 3-mm diameter tube, corresponding to left circumflex (LCX) artery, glued along the short axis of the column, at a 908 to the first.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The model used in these studies has been previously described [13]. Briefly, it consists of a 4-mm diameter silicon tube, corresponding to the left anterior descending (LAD) artery, glued along the long axis of a 7.5-cm diameter column, and a second, 3-mm diameter tube, corresponding to left circumflex (LCX) artery, glued along the short axis of the column, at a 908 to the first.…”
Section: Methodsmentioning
confidence: 99%
“…However, 75% of restenotic lesions in these studies were located at the ostium of the side branch [18][19][20][21]; this has been variously attributed to incomplete apposition between stent and vessel [12][13][14], under-expansion [21], and fracture of the side branch stent [22]. It has been shown that a wide (>708) bifurcation angle promotes the distortion of the side branch stent, which as a result, is not completely apposed to the vessel, even after KB inflation [12,13]. A wide bifurcation angle has also been demonstrated to be a risk factor for repeat TLR [23].…”
Section: Crush Stentingmentioning
confidence: 99%
See 1 more Smart Citation
“…6,14 In clinical practice, restenosis frequent occurs at the SB origin, a location that can easily be left without strut coverage in the case of provisional T-stenting, whether the SB is stented or not. 6,9 Incomplete SB coverage has been implicated as a possible cause of the high restenosis rate found at the SB origin. 6,8 It could be the consequence of different factors, such as recoil and struts malapposition at the SB origin (leading to a potential lack in drug application).…”
Section: Discussionmentioning
confidence: 99%
“…6,8 The high rate of SB ostium restenosis could be due to limited strut coverage in this area, with consequently inadequate drug distribution to the stented artery. 9 The aim of this study was to analyze the consequences of the kissing postdilatation technique (postdilatation by using simultaneous kissing balloon inflation) on 5 DESs commercially available in France, using microfocus x-ray computerized tomography (MFCT) and scanning electron microscopy (SEM). …”
mentioning
confidence: 99%